Uncovering the unseen: Metagenomic next-generation sequencing improves liver abscess diagnostics - Jing Zhao; Yao Wang; Dong Zhang; Juan Du; Yi Gao; Min-Ya Lu; Jia-Yu Guo; Hui-Ting Su; Xin-Fei Chen; Dong-Hua Wen; Shi-Yu Jia; Ying-Chun Xu; et al. (Journal of Infection and Public Health)
Background: This study retrospectively analyzed the metagenomic next-generation sequencing (mNGS) results and clinical data from patients with liver abscess (LA) to investigate the clinical value of mNGS in the diagnosis of LA. Methods: This retrospective observational study included patients with LA who were admitted to Peking Union Medical College Hospital (PUMCH) between April 2022 and July 2024. We comprehensively analyzed the final clinical etiological diagnosis, traditional pathogen detection through conventional microbiological testing (CMT), and mNGS results in terms of pathogen type and specimen turnaround time. Results: Among 60 patients with LA, 19 types of pathogens were identified. Using clinical etiological diagnosis as the standard, mNGS identified all pathogens, whereas CMT identified only 42.11 % of pathogens. The true-positivity rate of mNGS (86.67 %) was significantly higher than that of CMT (58.33 %; P < 0.001). The average specimen turnaround time for mNGS (57.66 h) was shorter than that for CMT (86.54 hours, P < 0.001). Conclusions: Compared with existing CMT, mNGS offers higher true-positive rates, broader pathogen coverage, and shorter specimen turnaround time. These advantages contribute to more accurate clinical diagnosis and treatment.